Development of functional chili sauce: effect of andaliman and bilimbi juices on antioxidant activity and vitamin C content - Maser, Wahyu Haryati; Panggabean, Efrillin Natasya; Ritonga, Ajuan; Hasdar, Muhamad; Laryea, Damian (My University, 2026)
This research investigated the influence of Zanthoxylum acanthopodium (andaliman) and Averrhoa bilimbi (bilimbi/Belimbing Wuluh) juice addition on the antioxidant activity and vitamin C content of chili sauce. A factorial Completely Randomized Design (CRD) was employed, involving two factors: andaliman concentration (0.3%, 0.5%, 0.7%) and bilimbi juice concentration (15%, 20%, 25%). The addition of andaliman significantly enhanced antioxidant activity (IC50) (P<0.01), while bilimbi juice also exerted a markedly significant effect (P<0.01). No significant interaction (P>0.05) was found between the two factors. The combination of 0.5% andaliman and 25% bilimbi juice resulted in a vitamin C content of 20.24 mg/100 g. These results demonstrate the potential of incorporating andaliman and bilimbi juice to develop functional chili sauce with improved antioxidant capacity and vitamin C enrichment. Furthermore, utilizing locally available plant-based ingredients such as andaliman and bilimbi supports sustainable food production through the valorisation of indigenous biodiversity and the reduction of synthetic additives. This approach contributes to food security by promoting functional products that enhance nutritional value, extend shelf life, and utilize renewable local resources.